Upaya Meningkatkan Keterampilan Menulis Kosakata Menggunakan Media Pembelajaran Kartu Flash pada Siswa Sekolah Dasar - Zahra kusumaningati; Ibnu Muthi (Politeknik Kampar, 2025)
This study aims to examine efforts to improve elementary school students’ vocabulary writing skills through the use of flash card learning media. The background of this research arises from the problem of students’ low writing skills, particularly in vocabulary mastery. Many students struggle to construct sentences due to limited vocabulary, low interest in writing, and monotonous teaching methods that fail to actively engage learners. This study uses a qualitative approach with a library research method by analyzing various theories and previous research findings from academic journals, books, and relevant articles. The results indicate that using flash cards is proven to be effective in enhancing students’ vocabulary mastery. Flash cards present visual information, such as images and words, which capture students' attention, facilitate understanding, and strengthen memory retention of new vocabulary. In addition, flash cards encourage active student participation because they can be integrated into fun learning activities such as word games, group discussions, and writing exercises. Through the application of flash cards, students are not only able to recognize and remember vocabulary but also learn to use it in meaningful sentence and paragraph contexts. Thus, the use of flash card media becomes an appropriate and innovative strategy for improving the vocabulary writing skills of elementary students. It contributes significantly to a more effective and engaging language learning process, fostering students’ confidence and motivation to write.